The Defense and Veterans Brain Injury Center Care Coordination Program Assessment of Program Structure, Activities, and Implementation - Martin, Laurie T. (RAND Corporation, 2013)
Survivors of improvised explosive device attacks often have traumatic brain injuries (TBIs). Those recovering from TBIs often find they must coordinate services across multiple systems of care, something that would be difficult even without cognitive challenges. This report documents RAND's assessment of a program designed to facilitate care coordination for such individuals.